2003
DOI: 10.1002/jemt.10290
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms of periodontal regeneration

Abstract: The periodontal ligament, located between the cementum and the alveolar bone, has a width ranging from 0.15 to 0.38 mm. Regeneration and homeostasis of the periodontal ligament are highly significant functions in relation to periodontal therapy, tooth transplantation or replantation, and orthodontic tooth movement. The purpose of this review is to discuss the regulatory mechanisms of regenerative and homeostatic functions in the periodontal ligament based on currently published studies and also on our own expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
162
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(181 citation statements)
references
References 106 publications
1
162
0
7
Order By: Relevance
“…In addition, 15 the PDL interface is composed of a heterogeneous cell population containing stem cell-like multipotent cells. [16][17][18] For the regeneration of functional periodontal complexes, the orientation of fibrous connective PDL tissues should exhibit perpendicular or oblique angulation to the tooth root surface. However, lack of control over the ligamentous fiber orientation remains a limitation for the regeneration of fibrous-mineralized tissue complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 15 the PDL interface is composed of a heterogeneous cell population containing stem cell-like multipotent cells. [16][17][18] For the regeneration of functional periodontal complexes, the orientation of fibrous connective PDL tissues should exhibit perpendicular or oblique angulation to the tooth root surface. However, lack of control over the ligamentous fiber orientation remains a limitation for the regeneration of fibrous-mineralized tissue complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Seo et al (2004) identified cells with the characteristic features of stem cells (e.g., self-renewal, clonogenicity and multi-tissue differentiation potential) resided in human periodontal ligament (PDL) tissue, a specialized soft connective tissue which anchors the teeth to the jaw bone and helps the tooth withstand natural chewing forces (Bartold et al 2000;Shimono et al 2003). The PDL stem cells (PDLSCs) have been shown to differentiate into osteoblasts and thus forming mineralized bone matrix both in vitro and in vivo (Chen et al 2006;Gay et al 2007;Gronthos et al 2006;Kemoun et al 2007;Seo et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The periodontal ligament is composed of a heterogeneous population of cells containing fibroblasts, osteoblasts and cementoblasts (Bartold et al, 2000;Gay et al, 2007;Lekic et al, 2001;Seo et al, 2004;Shimono et al, 2003). Early studies have suggested that the PDL tissue had regenerative or repair abilities when an injury was incurred by the periodontal tissue (Reviewed in Bartold et al (2005) and Shimono et al (2003)). Periodontal ligament stem cells were first isolated by Seo et al (2004) from impacted third molar adult teeth.…”
Section: Periodontal Ligament Stem Cellsmentioning
confidence: 99%